Exploration of Artificial Intelligence (AI) in Increasing Student Collaboration in Digital-Based Islamic Education Learning - Samsudin, Umar (Al-Hayat: Journal of Islamic Education, 2025)
Artificial Intelligence (AI) as a technology that is widely used in education today offers various features that facilitate the learning process. The use of AI can support students' collaborative learning. This study aims to explore the role of AI in improving student learning collaboration in digital-based Islamic Education at Al-Wasatiyah High School, Tangerang City. This research is qualitative research with a case study approach. The subjects of the research were two Islamic Education teachers, three students, and one IT assistant teacher. Data collection techniques were carried out by observation and interviews. Data analysis techniques were carried out by data reduction, data display, data verification, and conclusion. This study found that AI has the potential to improve students' collaborative learning, namely personalization of learning, fast access to learning resources, and provision of simulations and visualizations. Students' collaborative learning activities using AI are carried out through the stages of planning, implementing cooperative learning, and reflecting and evaluating. The main thing that is done at the implementation stage of collaborative learning is to encourage students to use group learning collaboration such as group discussions, problem-solving, and projects, guide students to use appropriate AI such as chatbot, intelligent recommendation systems, and adaptive learning platforms, find the right learning resources, and complete assignments. This study has limitations because it only uses descriptive analysis of limited data. Therefore, it is hoped that there will be further studies with more data coverage, such as the support of technological infrastructure owned by schools, the selection of various types of Artificial Intelligence (AI), and teacher skills in utilizing this technology effectively.